Simulation and test on separating cleaning process of flax threshing material based on gas-solid coupling theory - Dai, Fei; Song, Xuefeng; Guo, Wenjuan; Zhao, Wuyun; Zhang, Fengwei; Zhang, Shilin (International Journal of Agricultural and Biological Engineering, 2020)
In order to further clarify and improve the working performance of separating cleaning device of flax threshing material, and study the motion law and characteristics of components of flax threshing material, in this paper, numerical simulation was carried out on the separating cleaning process of flax threshing material based on CFD-DEM method. Simulation results showed that the components of flax threshing material were separated and cleaned under the influence of airflow field, meanwhile, variation curves of quantity and mean velocity of flax seeds in the separating cleaning system were obtained. By referring to streamline distribution of gas-solid coupling, the quantity variation law of components of flax threshing material with time was explored and their motion curves and variation tendency of average velocity were studied. Verification test results showed that the cleaning rate of separating cleaning device for flax threshing material was 92.66% with 1.58% of total separation loss. Compared with simulation results, the test results were 1.34% and 0.93% lower, showing that it is feasible to apply the gas-solid coupling theory and method to simulate the separating and cleaning operation of flax threshing material. Keywords: flax threshing material, separating cleaning device, hydromechanics calculation, discrete element, numerical simulation, test DOI: 10.25165/j.ijabe.20201301.5196 Citation: Dai F, Song X F, Guo W J, Zhao W Y, Zhang F W, Zhang S L. Simulation and test on separating cleaning process of flax threshing material based on gas-solid coupling theory. Int J Agric & Biol Eng, 2020; 13(1): 73–81.